2022
DOI: 10.3390/cancers14040968
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA LINC02470 Sponges MicroRNA-143-3p and Enhances SMAD3-Mediated Epithelial-to-Mesenchymal Transition to Promote the Aggressive Properties of Bladder Cancer

Abstract: Bladder cancer progression and metastasis have become major threats in clinical practice, increasing mortality and therapeutic refractoriness; recently, epigenetic dysregulation of epithelial-to-mesenchymal transition (EMT)-related signaling pathways has been explored. However, research in the fields of long noncoding RNA (lncRNA) and competing endogenous RNA (ceRNA) regulation in bladder cancer progression is just beginning. This study was designed to determine potential EMT-related ceRNA regulation in bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The prostate cancer progression was activated when the SMAD3 was upregulated [ 27 ]. SMAD3 could activate the TGF-β-induced EMT process of bladder cancer cells [ 28 ]. We can also observe that SMAD3 can promote the cancer progression, as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The prostate cancer progression was activated when the SMAD3 was upregulated [ 27 ]. SMAD3 could activate the TGF-β-induced EMT process of bladder cancer cells [ 28 ]. We can also observe that SMAD3 can promote the cancer progression, as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These results may explain the poor prognosis of patients with high AIGS. Notably, studies have shown that the E2F targets pathway is associated with chemotherapy resistance in bladder cancer [ 40 ]. Combined with the results of GSVA, patients with low AIGS may be more sensitive to chemotherapy, which paralleled our result in GSE52219 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the E2F4 TF was critical to repress MIR497HG transcription in BC cells. On the other hand, Linc02470 was identified in the lnCAR database as one of the most upregulated lncRNAs expressed during BC initiation and progression ( 84 ). In the context of TGF-β signaling, Linc02470 directly targeted the miR-143-3p , promoting SMAD3 expression, which consequently induced SNAI1, SNAI2, ZEB2, vimentin, and N-cadherin expression.…”
Section: Bladder Cancermentioning
confidence: 99%